2023
DOI: 10.55056/etq.635
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing descriptive writing of secondary school students through digital lesson contents in Zanzibar

Ali Juma Hamad,
Placidius M. Ndibalema,
Kulwa Yohana Matalu

Abstract: This study aimed to find out whether there was a significant difference in descriptive writing enhancement among secondary school students who were taught through digital lesson contents (DLCs) or not. A quasi-experimental pre-test and post-test through single group design was used for the study. One hundred twenty (120) students from three selected secondary schools were drawn using a purposive sampling technique. First, they were given a pre-test, and then teachers used DLCs for teaching descriptive writing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Also, these findings align with the study conducted by Ghomi and Redecker [10] in Germany, which observed that teachers' experience and attitude are essential factors as they influence teachers in using digital lesson contents for teaching and learning. It revealed that teachers' attitudes are essential for encouraging him/her to use DLCs in teaching and learning descriptive writing [13]. Therefore, in-service training is needed for all secondary teachers to change their mindset towards using DLCs for teaching and learning in secondary schools.…”
Section: Low Competence 4026%mentioning
confidence: 99%
“…Also, these findings align with the study conducted by Ghomi and Redecker [10] in Germany, which observed that teachers' experience and attitude are essential factors as they influence teachers in using digital lesson contents for teaching and learning. It revealed that teachers' attitudes are essential for encouraging him/her to use DLCs in teaching and learning descriptive writing [13]. Therefore, in-service training is needed for all secondary teachers to change their mindset towards using DLCs for teaching and learning in secondary schools.…”
Section: Low Competence 4026%mentioning
confidence: 99%